Dose-Dependent Pattern of Cochlear Synaptic Degeneration in C57BL/6J Mice Induced by Repeated Noise Exposure - Minfei Qian; Qixuan Wang; Zhongying Wang; Qingping Ma; Xueling Wang; Kun Han; Hao Wu; Zhiwu Huang (Neural Plasticity)
It is widely accepted that even a single acute noise exposure at moderate intensity that induces temporary threshold shift (TTS) can result in permanent loss of ribbon synapses between inner hair cells and afferents. However, effects of repeated or chronic noise exposures on the cochlear synapses especially medial olivocochlear (MOC) efferent synapses remain elusive. Based on a weeklong repeated exposure model of bandwidth noise over 2-20 kHz for 2 hours at seven intensities (88 to 106 dB SPL with 3 dB increment per gradient) on C57BL/6J mice, we attempted to explore the dose-response mechanism of prolonged noise-induced audiological dysfunction and cochlear synaptic degeneration. In our results, mice repeatedly exposed to relatively low-intensity noise (88, 91, and 94 dB SPL) showed few changes on auditory brainstem response (ABR), ribbon synapses, or MOC efferent synapses. Notably, repeated moderate-intensity noise exposures (97 and 100 dB SPL) not only caused hearing threshold shifts and the inner hair cell ribbon synaptopathy but also impaired MOC efferent synapses, which might contribute to complex patterns of damages on cochlear function and morphology. However, repeated high-intensity (103 and 106 dB SPL) noise exposures induced PTSs mainly accompanied by damages on cochlear amplifier function of outer hair cells and the inner hair cell ribbon synaptopathy, rather than the MOC efferent synaptic degeneration. Moreover, we observed a frequency-dependent vulnerability of the repeated acoustic trauma-induced cochlear synaptic degeneration. This study provides a sight into the hypothesis that noise-induced cochlear synaptic degeneration involves both afferent (ribbon synapses) and efferent (MOC terminals) pathology. The pattern of dose-dependent pathological changes induced by repeated noise exposure at various intensities provides a possible explanation for the complicated cochlear synaptic degeneration in humans. The underlying mechanisms remain to be studied in the future.